2014
DOI: 10.1098/rstb.2013.0302
|View full text |Cite
|
Sign up to set email alerts
|

The origin of human multi-modal communication

Abstract: One reason for the apparent gulf between animal and human communication systems is that the focus has been on the presence or the absence of language as a complex expressive system built on speech. But language normally occurs embedded within an interactional exchange of multi-modal signals. If this larger perspective takes central focus, then it becomes apparent that human communication has a layered structure, where the layers may be plausibly assigned different phylogenetic and evolutionary origins—especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
187
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(210 citation statements)
references
References 114 publications
9
187
0
7
Order By: Relevance
“…Many theories on the origins of language begin with two basic premises concerning the vocal behavior of nonhuman primates, especially the great apes. They assume that (1) apes (and other primates) can exercise only negligible volitional control over the production of sound with their vocal tract, and (2) they are unable to learn novel vocal behaviors beyond their species-typical repertoire (e.g., Arbib et al 2008;Burling 1993;Call and Tomasello 2007;Corballis 2002;Hauser 1996;Levinson and Holler 2014;Pinker 1994;Pollick and De Waal 2007;Premack 2004). These assumptions are often perpetuated through reference to a few notable reports.…”
Section: Introductionmentioning
confidence: 99%
“…Many theories on the origins of language begin with two basic premises concerning the vocal behavior of nonhuman primates, especially the great apes. They assume that (1) apes (and other primates) can exercise only negligible volitional control over the production of sound with their vocal tract, and (2) they are unable to learn novel vocal behaviors beyond their species-typical repertoire (e.g., Arbib et al 2008;Burling 1993;Call and Tomasello 2007;Corballis 2002;Hauser 1996;Levinson and Holler 2014;Pinker 1994;Pollick and De Waal 2007;Premack 2004). These assumptions are often perpetuated through reference to a few notable reports.…”
Section: Introductionmentioning
confidence: 99%
“…By enabling sophisticated forms of joint action, the human interaction engine paves the way for the emergence of cumulative culture and the development of social institutions. Levinson and Holler (2014) further suggested that the human interaction engine emerged as a step in an increasingly stratified system of communicative competencies that mark the evolution of modern human communication and has potentially evolved around 2 mya with the early forms of Homo.…”
Section: Is the Interactional Achievement Of Shared Intentionality Unmentioning
confidence: 99%
“…are expressions of a uniquely human set of capabilities and motivations for social interaction, the human "interaction engine". These include special communicative abilities, such as multimodal signal use (Levinson & Holler, 2014) and alternations of speaker-recipient turns in conversation (Levinson, 2016), special cognitive abilities, such as shared intentionality, and other ethological outputs, such as leave-taking rituals (Levinson, 2006a). Taken together, the elements of this engine enable human "cognition-for-interaction" (Levinson, 2006a) in a way that is independent of language, even though language has evolved as one of the primary means by which humans coordinate joint action.…”
Section: Is the Interactional Achievement Of Shared Intentionality Unmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary site of human language use is face-to-face conversation, suggesting that human language should be conceptualized as a fundamentally multimodal phenomenon (e.g., Bavelas & Chovil, 2000;Clark, 1996;Goldin-Meadow, 2003;Kendon, 2004Kendon, , 2014Levinson & Holler, 2014;Mondada, 2016;McNeill, 1992). Bodily signals, in particular, manual gestures, add a significant amount of meaning to what is being said.…”
Section: Language and The Bodymentioning
confidence: 99%